'What Is? What If? What Next?' Why institutions must urgently identify, support, and celebrate their student-parents – and imagining a world in which they do so. (28th February 2023) - Todd, Andrea
Students who have dependent children are 'relatively invisible in the policy and physical spaces of universities' (Moreau and Kerner, 2015: p.4), are 'ignored or only briefly mentioned' in governmental communications (Moreau, 2014: p2), and are impossible to track in terms of entrance to, performance at, or attrition rate from, higher education. There is no obligation on institutions in England and Wales to compile data on their students' family circumstances (Moreau, 2014), and as such student-parents at such institutions can remain unidentified and unsupported throughout their higher education journey. With the aim of adding urgency to the calls to take the first step in supporting student parents, this paper uses Hopkins' (Hopkins, R., 2019; 2022a) 'What is? What if? What next?' method to stimulate conversation about this overlooked cohort, and to visualise the ways in which studentparents could be supported and celebrated by their institutions if they were visible participants in higher education. The article underlines why the higher education sector should collect data on student-parents ('What is'); presents a vision of the university of the future which collects data from, and thus is able to support and celebrate, its student-parent population ('What if'); and urges higher education institutions, in the absence of a national requirement to do so, to compile data on an institutional level which in turn facilitates the retention, progression, achievement and satisfaction of this committed and motivated cohort ('What next').